TEACHERS’ PERCEPTIONS AND ATTITUDES TOWARDS THE IMPLEMENTATION OF SEXUALITY EDUCATION IN SCHOOLS OF THE KARAGANDA REGION - Zhuravleva, Olessya (Nazarbayev University Graduate School of Education, 2021)
As a conservative and traditional society Kazakhstani people have been embarrassed to discuss sexuality education with their children and teenagers. However, with increasing social issues such as family violence, increasing rates of teenage pregnancies and STIs demonstrate the necessity to implement school-based sexuality education. Access to sexuality education is an inherent right of any child, and the absence of it is critical. Despite worldwide development and implementation of sexuality education, it is still not provided in the Kazakhstani educational system due to being considered a culturally sensitive topic. It is possible to hope that school-based sexuality education will appear in Kazakhstani schools soon since it was suggested as a way to improve overall health and well-being by the Ministry of Healthcare of the Republic of Kazakhstan (2020). This research aimed to investigate primary and secondary school teachers’ attitudes and perceptions towards the implementation of school-based sexuality education. Teachers’ attitudes are relevant and should be considered since the success or failure of an educational reform depends on them. Qualitative research was employed to conduct this study, with the data gathered through a semi-structured interview. The research revealed the positive attitudes towards sexuality education regardless of the participants age, gender, years of teaching experience and urban or rural school location. The current study may have an influence on the realization of sexuality education in Kazakhstani mainstream schools. An effective, age appropriate school-based sexuality education will provide students with relevant and reliable information enabling them to make informed choices.
Keywords: traditional society; conservative society; Type of access: Gated Access; Karaganda region; sexuality education